Optimization of submerged steady-state fermentation process for glucose oxidase production by Aspergillus niger isolated from local environment - Hossain, Md. Emam; Alam, Md. Firoz; Razib, Mazedul Anwar; Alam, Mohammad Taufiq; Ahsan, Md. Shameem (Journal of BioScience and Biotechnology, 2020)
Glucose oxidase (GOX) is an enzyme with large scale applications in various industries. The aim of the present study is to optimize cost effective fermentation process for maximum production of glucose oxidase from locally isolated Aspergillus niger using as biosensor for detection of glucose level of body fluids. Among different five fungal strain, Aspergillus niger isolated from local onion sample was showed the highest activity. For low-cost glucose oxidase production, submerged steady-state fermentation process was applied. Medium composition and different parameter were studied to enhance production of glucose oxidase. The optimum enzymatic activity was obtained by using saccharose as carbon source and sodium nitrate as nitrogen source. The initial pH for the optimal production was found 5.5. Addition of K+ in fermentation medium increases enzyme activity while Mg2+ was found to inhibit glucose oxidase production by A. niger. Incubation time and culture morphology were also examined to increase glucose oxidase production.